Mapping evidence on HIV status awareness among key and vulnerable populations in sub-Sahara Africa: a scoping review protocol - Avoka, Clement; Adzordor, Patience; Bawontuo, Vitalis; Akila, Diana A.; Kuupiel, Desmond (Systematic reviews, 2020)
Background Human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS) continue to be a major public health issue, especially in sub-Sahara Africa (SSA). Literature shows significant HIV status awareness, testing, and treatment have generally improved among the population since the inception of the UNAIDS 90:90:90 programme. Despite this, it is possible literature gaps exist that require future research to inform in-country programmes to improve the gains post-UNAIDS 90:90:90 programme. This study, therefore, aims to synthesize literature and describe the evidence on HIV status awareness among key and vulnerable populations in SSA focusing on the first UNAIDS 90 since it is essential for treatment initiation. Method This systematic scoping review will be guided by the framework proposed by Arksey and O’Malley and improved by Levac and colleagues. Literature searches will be conducted in PubMed, SCOPUS, CINAHL, Google Scholar, and Science Direct from 2016 to 2020. A snowball approach will also be used to search for relevant articles from the reference of all included studies. This study will include both published and grey literature, articles that include HIV key and vulnerable populations, HIV status awareness, and evidence from SSA countries. Two reviewers will independently conduct the abstract and full-text article screening as well as pilot the data extraction form. Thematic content analysis and a summary of the themes and sub-themes will be reported narratively. Discussions The evidence that will be provided by this study may be useful to inform in-country programmes to improve the gains made post-UNAIDS 90:90:90 programme from 2021 onwards. This study also anticipates identifying literature gaps to guide researchers interested in this field of study in the future. Peer review journals, policy briefs, and conference platforms will be used to disseminate this study’s findings.